COST AND TIME STUDY ON THE REHABILITATION PROJECT OF THE DIR. POLDER TAMBAK HANYAR IRRIGATION NETWORK IN BANJAR REGENCY USING THE EARNED VALUE METHOD - Rusbandi, Indra; Yuliana, Candra (Universitas Lambung Mangkurat, 2026)
The implementation of construction projects often faces various issues that cause discrepancies between actual results and plans, both in terms of cost and time. Similar problems also occur in the Rehabilitation Project of the DIR. Polder Tambak Hanyar Irrigation Network in Banjar Regency, making it necessary to conduct an evaluation to ensure the project can return to running according to plan. One effective evaluation method that can be used is the earned value method, which allows for a comprehensive analysis of project performance by comparing the value of completed work with planned costs and timelines, enabling the project to identify issues and make appropriate decisions to address the discrepancies. In the earned value method, three indicators are used: planned value, earned value, and actual cost. This method also includes variance analysis, performance index analysis, and cost and time estimation analysis for project completion. The goal is to identify deviations related to costs and time, allowing for control measures to be implemented to manage costs and time effectively. The results of the analysis using the earned value method show that, in terms of time performance, delays occurred from the first week to the eighth week, with a Schedule Performance Index (SPI) below 1. Meanwhile, in terms of cost performance, the project experienced losses during the first, second, third, and fifth weeks, with a Cost Performance Index (CPI) below 1.Keywords: earned value method, planned value, earned value, actual cost, cost and time evaluation.